2009
DOI: 10.2527/jas.2008-1108
|View full text |Cite
|
Sign up to set email alerts
|

Growing steers grazing high versus low endophyte (Neotyphodium coenophialum)-infected tall fescue have reduced serum enzymes, increased hepatic glucogenic enzymes, and reduced liver and carcass mass1

Abstract: It is well established that grazing Neotyphodium coenophialum-infected forages results in reduced BW gain and serum prolactin concentrations of cattle. The objective of this study was to determine the potential effects of toxic endophyte-infected tall fescue consumption on blood metabolites, carcass characteristics, and content of proteins critical for AA metabolism in the liver, kidney, and LM tissue of growing steers. Steers grazed a low toxic endophyte (LE; 0.023 microg/g ergot alkaloids) tall fescue-mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 55 publications
6
59
2
Order By: Relevance
“…Disruption of lipid homeostasis is a feature of FT; dyslipidemia, as well as suppressed serum cholesterol and triglycerides, all have been associated with FT previously (22,74). The early decreases in the Erysipelotrichaceae, along with the previously reported decreases in enzymes associated with lipid metabolism in FT (e.g., lipase) (75,76), could contribute to the dyslipidemia.…”
Section: Discussionmentioning
confidence: 92%
“…Disruption of lipid homeostasis is a feature of FT; dyslipidemia, as well as suppressed serum cholesterol and triglycerides, all have been associated with FT previously (22,74). The early decreases in the Erysipelotrichaceae, along with the previously reported decreases in enzymes associated with lipid metabolism in FT (e.g., lipase) (75,76), could contribute to the dyslipidemia.…”
Section: Discussionmentioning
confidence: 92%
“…Examples of studies that have measured serum prolactin concentrations in cattle on pasture have reported levels of 36.0 [19], 50 [20], 108 [21], and 194 ng/mL [22] for control or endophyte-free pasture treatments. Conversely, for these same studies prolactin concentrations measured in steers on the ergot alkaloid-containing pasture treatment were 3.6 [19], 16 [20], 17 [21], and 82 ng/mL [22]. It is important to note that this wide range in reported concentrations makes comparisons across studies tenuous, due to the numerous factors that can influence the measurement of prolactin at a single point in time.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports (Settivari et al, 2006(Settivari et al, , 2008Brown et al, 2009) indicate other molecular mechanisms that may contribute to the syndrome of ergot alkaloid intoxication such as fescue toxicosis. A survey of the literature suggests that transport proteins, as a class, may be particularly susceptible to the presence of ergot alkaloids.…”
Section: Known and Potential Regulation Of Cellular Transport Mechanimentioning
confidence: 95%